Eksistensi Takhta Suci Vatikan: Relevansinya terhadap Penundukan Diri Suatu Negara - Yanubi, Yustinus Stevanus; Wattimena, Josina Augustina Yvone; Peilouw, Johanis Steny Franco (Uti Possidetis: Journal of International Law, 2022)
Abstract This article discusses the existence of the Holy See in the international community, especially in terms of religious spirituality to appoint bishops as part of their rights as subjects of international law. The existence of the Holy See as a subject of international law is recognized through the recognition of states against the decision to appoint bishops by the Pope. This article uses a normative juridicial method with the main source being legal materials containing normative legal rules. The decision to appoint bishops by the Pope can basically make countries submit to themselves. This is reflected in various forms of recognition by countries such as positive legal recognition, political recognition, and tacit recognition. In the context of the case with the Chinese government, it can be seen that China has made tacit recognition of the Pope's authority in appointing bishops. So that it can be firmly said that the recognition is a respect for the rights of the Holy See in accordance with international law. Â